Hubungan Tingkat Pengetahuan dan Sikap Pasien Terhadap Kepatuhan Minum Obat Anti Hipertensi di UPTD Puskesmas Kabawetan - ardianti, jeni; Ramon, Agus; Oktavidiati, Eva; Yanuarti, Riska (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2025)
Background: Hypertension is one type of Hazardous disease that can cause death. One of the global hopes for PTM is to reduce the number of hypertension by 33% in 2010 and 2030. Compliance in taking medication for hypertension sufferers is certainly important because it can control blood pressure by taking medication regularly and can overcome complications of the disease. Based on observations at the UPTD Puskesman Kabaweran, hypertension is one of the most common types of disease. This study aims to see the relationship between the level of knowledge and attitudes of patients on compliance with taking antihypertensive drugs in the UPTD Puskesmas Kabawetan Work Area. Metodh: This study employed a cross-sectional design and a quantitative methodology. The sample used in this research was 86 respondents who suffered from hypertension at the Kabawetan Community Health Center UPTD. Result: The results of the chi square analysis showed that there was a relationship between knowledge and compliance with taking medication (P = 0.016), and there was a relationship between attitudes towards compliance with taking medication (P = 0.011). Conclusion: Thus, it can be concluded that there is a relationship between knowledge and attitude with medication compliance. Therefore, the researcher suggests that respondents check their blood pressure regularly so that their blood pressure can be controlled every day. Keywords: Hypertension, Medication Compliance